Interpol’s Efforts Against Human Trafficking by Non-Procedural Migrant Worker Networks in East Nusa Tenggara: Leveraging Legal Assistance Treaties - Aulya, Layla Putri; Arifin, Ridwan; Sabri, Zaharuddin Sani Ahmad; Nte, Ngaboawaji Daniel (International Law Discourse in Southeast Asia, 2024)
This paper delves into the proactive measures adopted by Interpol to counter the pervasive issue of human trafficking, focusing specifically on the activities of non-procedural migrant worker networks in East Nusa Tenggara. Human trafficking remains a grave violation of human rights globally, with vulnerable migrant workers often falling victim to exploitation and abuse. In regions like East Nusa Tenggara, where such networks operate with relative impunity, concerted efforts are necessary to dismantle their operations and bring perpetrators to justice. Interpol plays a crucial role in this endeavor by leveraging legal assistance treaties to enhance international cooperation in combating transnational crimes, including human trafficking. Through these treaties, Interpol facilitates information exchange, joint investigations, and coordinated law enforcement actions among member countries, thereby strengthening the collective response to this multifaceted challenge. In East Nusa Tenggara, where the complexities of jurisdiction and cross-border activities complicate law enforcement efforts, Interpol's involvement becomes particularly significant. By collaborating with local law enforcement agencies and leveraging its global network of resources, Interpol can identify, disrupt, and dismantle the networks involved in human trafficking. This paper will explore the mechanisms through which Interpol utilizes legal assistance treaties to support investigations, apprehend perpetrators, and rescue victims of human trafficking in East Nusa Tenggara. Additionally, it will assess the effectiveness of these strategies in mitigating the impact of non-procedural migrant worker networks and advancing the overarching goal of eradicating human trafficking. Through a comprehensive analysis of Interpol's efforts in this context, this paper aims to contribute to the discourse on international law enforcement cooperation and the fight against human trafficking.